Government Communication And Society In Disaster Education and Mitigation Preventing the Impact of Sea Rituals in Payangan Beach Tourism, Jember Regency - Juariyah, Juariyah; Adawiyah, Putri Robiatul (POLITICO, 2023)
This study aims to determine the communication strategy of the Government and the community in education and disaster mitigation to prevent the impact of the Payangan Beach Sea Ritual, Jember Regency. Government communication carried out by the village head of Payangan village is very important considering that the Payangan village community recently had a case of missing residents due to being dragged by the sea waves after carrying out a ritual at Payangan Beach on Sunday, February 13 2022. Interviews were conducted with the village head, Basarnas team and the community around, to explore the existing data after that the results of the interviews were described and then the data were analyzed. Based on the research results obtained the following conclusions. Effective Government Communication carried out by Village Officials with the community includes: Disaster Risk Information, Outreach, Coordination of Disaster Management Teams, Installation of Warning Signs, Disaster Simulation, and Building One Information Emergency Communication Posts and Networks. The government's strategy includes outreach and education, supervision, compromise and partnership with environmental organizations, imposition of sanctions. Government Communication Media, including social media such as Facebook, Instagram, Twitter, and the like can be a very effective medium for conveying information related to dissemination of disasters when picking the sea. The government can use social media to post information, photos and videos that can attract public attention. Official Website, SMS Blast, Radio and Television. Barriers that occur in communicating between the government and the community, Limited access to information, Lack of public awareness: Limited resources, Lack of coordination between the government and related institutions and the community. Village Government efforts include: involving MUSPIKA to carry out evacuation during incidents and full supervision afterwards. The suggested solution is for the community to be more careful, alert and anticipate the presence of outsiders who enter without SOP and report to the relevant parties during related sea rituals and be more vigilant about deviating currents. Conducting more intensive outreach to the community through the Hamlet Head. Suggestions for the future are for the government and organizers to use both online and print media, banner boards, billboards, supporting facilities for outreach so that people are more careful in sea ritual activities as well as tourism and activities at sea. Be aware of activities during extreme weather seasons and carry out more supervision and assistance during certain seasons with potential disasters. Coordinate with other agencies and institutions related to disaster mitigation management at sea tourism sites. Improving the management of marine tourism management in Payangan and others. Involve all stake holders in the management of both Government, Private and Community.